(3fXe GdeYdheGJ GdeGdjI (B:s (3CSSgG GdfXQjI h HfGA bhGYO HjGfGJgG (B/s - (3eMSf, UHGM QMjeIs; (3GdTjHGfj, aJMj CMeO s; (3RQjHI, YHO GdaJGM GHQGgje s ((3YeGf(B: s (3GdhQGb ddfTQ hGdJhRjY(B, s, 2011)
(3fXe GdeYdheGJ HUaI YGeI , fXe OYe GdbQGQGJ h fXe eYdheGJ GdGfJGL , fXe GdeYdheGJ GdeGdjI , HfGA bhGYO HjGfGJ ZSjd GdCehGd h HfGA bhGYO HjGfGJ eGdjIs
(3bGFeI GdLOGhd U(B.09(3; bGFeI GdGTcGd U(B.11s
Keywords: (3GdeGdjI GdYGeIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s; (3fXe GdeYdheGJ(B- (3GdeGdjIs